2015
DOI: 10.1179/1743132815y.0000000010
|View full text |Cite
|
Sign up to set email alerts
|

Association between nocturia and anxiety in Parkinson's disease

Abstract: Based on these findings, we can conclude that anxiety and nocturia are not entirely independent symptoms in all PD patients. Thus, addressing anxiety may improve nocturia in PD or vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Several specific nonmotor symptoms are also known to be associated with LUT dysfunction [30, 31]. Our results suggested a possible connection between RBD and LUT dysfunction in PD.…”
Section: Discussionsupporting
confidence: 58%
“…Several specific nonmotor symptoms are also known to be associated with LUT dysfunction [30, 31]. Our results suggested a possible connection between RBD and LUT dysfunction in PD.…”
Section: Discussionsupporting
confidence: 58%
“…Yeo et al 20 described nocturia as the most common urinary tract complaint in patients with PD (>60%) and attributed it to detrusor muscle overactivity, while urgency was found at 33%–54%. Rana et al 21 reported a significant association between anxiety and nocturia in patients with PD, with greater significance found for male patients as compared with female patients, and suggested that addressing anxiety may help nocturia.…”
Section: Discussionmentioning
confidence: 99%
“…One study in which 314 PwPD were enrolled reported a significant association between nocturia and anxiety, which was more prominent in male patients. The authors suggest that multiple instances of awakening during the night due to the need to void induce a state of distress for these patients, and contribute to a vicious circle in which nocturia, anxiety, interrupted and inadequate sleep, and fear of falling are involved [54]. According to Benli et al, lower urinary dysfunction may be a risk factor for the development of anxiety and depression [55].…”
Section: Discussionmentioning
confidence: 99%